PENGARUH IMPLEMENTASI UU NO.22 TAHUN 2009 TENTANG LALU LINTAS ANGKUTAN JALAN (LLAJ) TERHADAP DISIPLIN PENGEMUDI ANGKUTAN KOTA DI KOTA BOGOR - Bunyamin, Ijang; Salbiah, Euis; Seran, YGG (Fakultas Ilmu Sosial Ilmu Politik Universitas Djuanda Bogor, 2015)
The objective of this research is to know the influence of implementation of Law No.22 of 2009 in its influence on the discipline of public transportation drivers in the city of Bogor, how a causal effect on the implementation of Law No. 22 of 2009 on the LLAJ. The method used in this research is associative. The research aims to determine the relationship between two or more variables. With this research it will be constructed a theory that could serve to explain, predict, and control a symptom. For data analysis used the formula Weight Mean Score (WMS). Population employee who becomes the object of observation of 70 people and the population of the city transport driver and the driver as much as 3412 to determine the sample size used Yamane formula so that the number of samples used to 41 employees and 97 DLLAJ transport drivers in the city of Bogor. To search for correlation using Spearman Rank Correlation formulas with the help of calculations using SPSS software version 20.0.The results showed Effect of Implementation of Law No. 22 of 2009 on the Discipline of public transportation drivers in the city of Bogor was pretty good. It can be seen that the significance of 0.000 is less than 0.05, the null hypothesis is rejected, the conclusion that there is a close and meaningful relationship between the application of Law No. 22 of 2009 Implementation of the Work Discipline driver of public transportation in the city of Bogor. Of the output data obtained Spearmans rho correlation coefficient of 0.919. Because the value is closer to 1, the relationship between the implementation of the Work Discipline is strong. Rank too high a value on the positive and that is equal to 0.680. The value of the coefficient is positive (+), meaning that if higher then Item Implementation Work Discipline will increase if Item Implementation of high or low it will affect the Work Discipline low as well. The relationship between the implementation of the Work Discipline significant influence (strong). Keywords: Implementation, Discipline, Public Transportation, Transportation Management